Synthesis, growth and characterization of magnesium chloride doped L-alanine cadmium chloride single crystal: For nonlinear optical application - Dessale Alemu; Idris Shafi; Tizazu Abza (East African Journal of Biophysical and Computational Sciences)
The aim of this research was to synthesize and characterize pure and magnesium chloride (MgCl2) doped L–alanine cadmium chloride (LACC) single crystals. Pure and MgCl2 doped LACC single crystals were synthesized by solution method with slow evaporation solution growth technique at room temperature. The single crystal X-ray diﬀraction studies of pure, 1 and 2 mol% MgCl2 doped LACC single crystals revealed monoclinic crystal structure with C2 space group. The optical properties of pure and MgCl2 doped LACC single crystals investigated by UV–VIS/NIR spectrometer confirmed that the crystals were transparent in the wavelength range of 230-1100 nm. The optical band gap energy of pure and doped LACC single crystals were found to have the same value of 5.4 eV. The energy-dispersive X-ray analysis indicated the incorporation of magnesium and chlorine atoms in LACC single crystal. The second harmonic generation eﬃciency of 1 and 2 mol% MgCl2 doped LACC crystals were analyzed by Kurtz-Perry powder technique and found to be 1.75 and 2 times greater than that of the standard potassium dihydrogen phosphate crystal, respectively.